Cutting it Out : a Journey through Psychotherapy and Self-Harm. - Smith, Carolyn (Jessica Kingsley Publishers, 2005)
'Cutting it Out is an intriguing detective novel in which a young woman discovers why she cuts her flesh. Her self-attacks, seemingly so incomprehensible and inhuman, cannot withstand the hidden truths that emerge from the deepest layers of her mind. Cleverly crafted and well-written, the novel is a realistic and solid read.'. - Armando Favazza MD, author of Bodies Under Siege and Professor of Psychiatry, University of Missouri. 'My room is untidy. By my bed a pile of books and newspapers is used as a handy table for three empty mugs of tea and a plate of toast crumbs. By the side of the 'tabl.